Optimal Scheduling Method for a Regional Integrated Energy System Considering Joint Virtual Energy Storage - Xu Zhu; Jun Yang; Yuan Liu; Chang Liu; Bo Miao; Lei Chen (IEEE Access, 2019)
Energy storage equipment is an important part of integrated energy systems, but the construction and operational costs of it are great. Therefore, it's difficult to apply energy storage equipment on a large scale. As an alternative measure, adjusting controllable loads including electric vehicles (EVs) and air conditioning loads jointly can transfer loads across time periods and reduce variation difference between heat and electric loads. These controllable loads can be regarded as “virtual energy storage system”. Managing the charging of EVs and heat storage of buildings, a joint virtual energy storage system including electric energy storage and thermal energy storage is proposed in this paper. Then, these models are integrated into a scheduling model for regional integrated energy system (RIES). The charging/discharging power management of joint virtual energy storage systems can be realized by arranging the charging of EVs based on vehicle-driven rules and by adjusting building indoor temperatures within the temperature comfort range. Finally, simulations are carried out to demonstrate the effectiveness of the scheduling method. Simulation results show that the RIES optimal scheduling model considering joint virtual energy storage can reduce operational costs. The stability of RIES is improved with the combination of virtual electrical and thermal energy storage.